Optogenetic Tools for Manipulating Protein Subcellular Localization and Intracellular Signaling at Organelle Contact Sites. Issue 3 (3rd March 2021) - Benedetti, Lorena
Abstract: Intracellular signaling processes are frequently based on direct interactions between proteins and organelles. A fundamental strategy to elucidate the physiological significance of such interactions is to utilize optical dimerization tools. These tools are based on the use of small proteins or domains that interact with each other upon light illumination. Optical dimerizers are particularly suitable for reproducing and interrogating a given protein‐protein interaction and for investigating a protein's intracellular role in a spatially and temporally precise manner. Described in this article are genetic engineering strategies for the generation of modular light‐activatable protein dimerization units and instructions for the preparation of optogenetic applications in mammalian cells. Detailed protocols are provided for the use of light‐tunable switches to regulate protein recruitment to intracellular compartments, induce intracellular organellar membrane tethering, and reconstitute protein function using enhanced Magnets (eMags), a recently engineered optical dimerization system. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Genetic engineering strategy for the generation of modular light‐activated protein dimerization units Support Protocol 1 : Molecular cloning Basic Protocol 2 : Cell culture and transfection Support Protocol 2 : Production of dark containers for optogenetic samples Basic Protocol 3 : Confocal microscopy and light‐dependent activation of the dimerization system Alternate Protocol 1 : Protein recruitment to intracellular compartments Alternate Protocol 2 : Induction of organelles' membrane tethering Alternate Protocol 3 : Optogenetic reconstitution of protein function Basic Protocol 4 : Image analysis Support Protocol 3 : Analysis of apparent on‐ and off‐kinetics Support Protocol 4 : Analysis of changes in organelle overlap over time